Aksiologi Ilmu dalam Perspektiktif Barat dan Islam: Analisis Filosofis Atas Persamaan dan Perbedaannya - Pimpinan Abaik Simamora; Salahuddin Harahap (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
The axiology of science is a branch of the philosophy of science that examines the values, goals, and orientations of scientific knowledge utilization. This article aims to philosophically analyze the concept of the axiology of science from Western and Islamic perspectives, highlighting their fundamental similarities and differences. This research employs a qualitative method, employing a literature review approach with descriptive-analytical and comparative methods. The results of the study indicate that in the Western philosophical tradition, the axiology of science has developed historically, from the search for the highest good in classical times to the tendency towards value relativism in the modern and postmodern eras, with human rationality as the center of value determination. Meanwhile, the axiology of science in Islam is rooted in monotheism as a metaphysical foundation, with revelation as the primary source of values ​​and reason serving as an interpretive instrument. Despite paradigmatic differences, both traditions affirm that science cannot be separated from moral dimensions and ethical responsibility. This article concludes that dialogue between Western and Islamic axiology is essential for building a scientific paradigm that is not only rational and progressive, but also moral, just, and oriented towards the welfare of humanity.